Pascual Bolaños y Novoa: La percepción de un jurista de la Crisis de 1808 - Moreno Pastor, Luis (Cuadernos de Historia del Derecho, 2011)
The commotion that shook the Spain of principles of 19th century, produced among others factors by a deep crisis of the institutions and their system of government, would lead to the landslide of absolutism and the birth of the first Spanish liberalism. Pascual Bolaños was a witness of his time and the protagonist of some excellent episodes, leaving his thought, at least partly, in his writings.